ASSESSMENT OF PROCESSING CAPACITY OF RAILWAY STATIONS BASED ON STATISTICAL ANALYSIS METHODS - Taran, Ihor; Tilemisova, Aigul; Kozachenko, Dmytro; Verlan, Anatoliy; Grevtsov, Serhii (Journal of Applied Engineering Science, 2025)
The purpose of the study is to improve the methods of assessing the processing capacity of railway stations based on scientific observation data. The paper considers a large private station that provides transport services to port terminals when performing railway and water transportation. The research is performed based on methods of analysis of time series and theory of operation of railways. The study established the maximum permissible volume of work for the port station and also assessed the impact of the combination of diverse types of goods on the amount of its processing capacity. The scientific novelty of the work is to improve the methods of evaluating the processing capacity of railway stations based on the methods of statistical data analysis. Unlike the existing method, the method allows you to more accurately consider local features of stations. The practical value of the results obtained is that they allow to predict the work of the station in the conditions of accidental flow of port terminals requests for servicing and avoid overload. This enables the station management to develop more efficient strategies for managing its work.